CONSUMER SOCIETY IN UMAR KAYAM’S JALAN MENIKUNG A STUDY OF JEAN BAUDRILLARD’S POSTMODERNISM - Suharmono, Suharmono (ATAVISME, 2023)
Abstract: The research aims to reveal the consumer society in Jalan Menikung, a novel written by Umar Kayam. The theoretical framework used is the postmodern theory of Jean Baudrillard. Baudrillard reveals the characteristics change of culture in contemporary society and introduces the characteristics of Western society as a simulation society. The method used in this study is qualitative. The material was obtained from literature and analyzed using the conception of Baudrillard. The important concept used is the change in value, simulation, simulacra, hyperreality, and consumer society. The results of the study show that in the novel Jalan Menikung, there is a change in value that occurs in the form of consumerism. This consumerism is in the form of consuming clothes, consuming food, or drinks, consuming certain buildings, consuming certain luxury goods, consuming in orgies, consuming in the use of power, and consuming in high-class associations. Simulation processes of consumption in Jalan Menikung happen on the development of technology, especially information technology and language signs. In Jalan Menikung Umar Kayam describes the consumer society as a complicated culture intertwined.